Aplikasi Tumbuh Balita (ATULITA) Memantau Pertumbuhan Balita Di Posyandu Jamblang - Ika Maruya Kusuma; Taufik Hidayat; Siti Nurmiati; Amelia Febriani (Institut Sains dan Teknologi Nasional, 2023)
ABSTRACT The monitoring of toddler growth is currently limited, involving manual recording of quantitative measures such as weight, height, and head circumference. This research aims to enhance partners' understanding of the usage of the Toddler Growth Application (Atulita), which not only includes quantitative measurements but also incorporates qualitative nutritional screening. The methods employed include observation, interviews, and literature review. The research reveals that the Atulita Application is designed and built on the Android platform, accessible through a smartphone. On average, there is a 11.7% improvement in partner engagement with the Atulita Application as a result of the study.